Kekuatan Diskursif Cerpen Jangan Pulang Jika Kamu Perempuan dalam Membentuk Pandangan Dunia Siswa Sekolah Menengah Atas - Satrya HD, Dharma; Riyana Rizki Yuliatin; Moh. Irfan; Lalu Mas’ud; Mudarman (Insan Kreasi Media, 2023)
This article aims to introduce the latest Indonesian Lombok short stories as well as look at the discursive power of these short stories in shaping the worldview of high school students. This article highlights the short story's ability to influence how students make decisions if the students are in socio-cultural conditions as shown by the short story. This article is an effort to socialize Lombok culture in Indonesian literature which is designed as a community service scheme. The service program uses structural theories and methods and discourse analysis. The results of the community service show that the short story raised the awareness of high school students in understanding the Sasak culture of elopement. Students previously understood the culture of elopement as a culture that is taken for granted, but through the justice scheme, students realized that the Sasak culture of elopement is a culture that favors men. In this context, the worldview of high school students tends to reject tradition and chooses to be a modern person, refusing to be governed by custom.